TEACHING READING COMPREHENSION BY USING THINK ALOUD STRATEGY OF SMAN 9 BANYUASIN (Universitas Muhammadiyah Palembang, 2023)
The objective of this research was to find out whether or not it is effective to use think aloud strategy in teaching reading comprehension to the eleventh grade students at SMAN 9 Banyuasin. This research used quasi-experimental. The sample were 61 students which taken through convenience sampling. The data were analyzed by using independent sample t-test. . The result of t-obtained was 4.649, t- table was 1.67. As we know, t-obtained was higher than t-table. It means that it is effective to teach reading analytical exposition text by using think aloud Strategy to the eleventh grade students of SMAN 9 Banyuasin.